SPICES AND THEIR INFLUENCE ON THE ACTIVITY OF INTESTINAL PHOSPHATASES - Amenah Jafarey; Moazzam Shahid; Saeeda Baig (ziauddin University, 2019)
Background: Southeast Asian recipes for everyday meals incorporate the use of several spices such as onions, red chillies, turmeric, coriander, cumin, black pepper, garlic and ginger, while cardamom, cinnamon, aniseed, caraway, clove etc are added when preparing festive dishes. The regular use of seasoning spices raises the question of how they may interact and influence the digestive process. The objective of this study was to find out the effect of fourteen seasonal spices on the three intestinal phosphatases: alkaline phosphatase (AlkPase), adenosine triphosphatase (ATPase), and acid phosphatase. Methods: The experiment was conducted on rabbits since they are not exposed to spices. A homogenate was made out of the intestines of rabbits. Fourteen commonly used spices were ground, dried, and aqueous and lipid extracts of each spice were prepared. Alk'pase, Acid'pase and ATP'ase were assayed with and without spices using a calorimetric method. Results: Spices, in general, decreased the activity of enzymes. Lipid extracts are the active portion of spices, as they produced significant activation and inhibition. Lipid extract of garlic activated all three enzymes. General inhibition of the phosphatases was produced by the extracts of cinnamon, caraway and clove. Lipids of chillies activated Acid'paseand Alk'pase, while their aqueous extract inhibited both. Ginger inhibited Alk'pase and ATP'ase, while cumin, coriander, anise and turmeric inhibited Acid'pase and ATP'ase. Conclusion: Generally, spices influence the activity of enzymes by either inhibiting or activating them. However, more focused studies need to be conducted on spices and their influence on physiological process for diagnostic and therapeutic purposes in the future.